Application of a new fuzzy Dematel–Todim hybrid algorithm in port dredging project management. Issue 3 (5th September 2020) - Khorram, Saeed; Bahrami, Ali
Abstract : As an effective evaluation of the productivity of dredging projects is an important element in the success of loading/unloading operations at ports, this study was carried out to find common reasons why dredging projects incur unintended damage at Anzali port open seas/coasts. It was found that the fuzzy decision making trial and evaluation laboratory (Dematel) method and experts' opinions can be effectively used in dredging problems in practice considering risk interactions. Of 58 identified risks, the top ten were selected using a probability–effect diagram and then, for a more precise ranking, their rates of effects on one another were evaluated using the fuzzy Dematel approach. Finally, using a combination of fuzzy sets and the Dematel technique, the ten top risks were ranked by multiplying four factors: effects on the project, occurrence probability, effects on/of other risks. To demonstrate the capabilities of the proposed approach, it was used in the dredging project of the large and important Iranian port of Anzali. The results of this research were used to propose a risk prioritisation model considering the complex interactions of risks in port dredging projects. Some suggestions are made regarding how to lessen the risks and enhance safety measures.